2008
DOI: 10.1351/pac200880081747
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature gradient HPLC and LC-NMR for the analysis of complex polyolefins

Abstract: The synthesis and characterization of polyolefins continues to be one of the most important areas for academic and industrial polymer research. One consequence of the development of new "tailor-made" polyolefins is the need for new and improved analytical techniques for the analysis of polyolefins with respect to molar mass and chemical composition distribution. The present article briefly reviews different new and relevant techniques for polyolefin analysis. Crystallization analysis fractionation is a powerfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 63 publications
0
18
0
Order By: Relevance
“…For comparison, a separation of PE from PP with molar mass below about 20 kg/mol was not possible using precipitation-redissolution chromatography with EGMBE as the mobile phase. 36,37 We note that oligomers of PE and PP with smaller molar mass evaporate at 260 C in the ELSD and therefore do not yield a detector response.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…For comparison, a separation of PE from PP with molar mass below about 20 kg/mol was not possible using precipitation-redissolution chromatography with EGMBE as the mobile phase. 36,37 We note that oligomers of PE and PP with smaller molar mass evaporate at 260 C in the ELSD and therefore do not yield a detector response.…”
Section: Resultsmentioning
confidence: 94%
“…The group of Prof. H. Pasch (present address: University of Stellenbosch, Stellenbosch, South Africa) in Darmstadt has recently published the first HPLC procedures for the separation of PE and PP. [36][37][38][39][40][41][42][43] PE or PP were selectively adsorbed in the zeolites [40][41][42][43] or HPLC separation has been based on selective precipitation of PE. 36,38 Lehtinen und Paukerri 44 found that ethylene glycol monobutyl ether (EGMBE) dissolves isotactic polypropylene (iPP) but not linear PE.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, an enormous potential of this technique becomes obvious when considering the hyphenation of 2D HT‐LC (or HT‐LC) systems with post separation characterization. A direct benefit lies in the on‐line hyphenation, e.g., with NMR in on‐flow mode, where solvent signal suppression by special pulse sequences is required. But in the same sense an improved amount of analyte is helpful for off‐line characterization by for example DSC, where the now standard DSC instrumentation and methods may then be used instead of HyperDSC and thus quantitative data can be obtained.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it would be desirable to replace TCB by an alternative solvent in future. [52,53], coupled high-temperature SEC with FTIR (HT SEC-FTIR) [53][54][55][56][57][58][59], coupled HT SEC with NMR (HT SEC-NMR) [18,60] and with DSC (HT SEC-DSC) [57], and also used asymmetrical flow field-flow fractionation to analyze polyolefins [61]. In the meantime, novel HPLC systems applicable on the analysis of polyolefins have been developed, which will be described in the following text.…”
Section: Sec Of Polyolefinsmentioning
confidence: 99%
“…In this chromatographic system, PE precipitated from the mobile phase because a nonsolvent 1-decanol was used as eluent. The precipitation enabled the separation of isotactic PP from linear PE [60,64] as well as the separation of ethylene-propylene copolymers [66,67] according to their chemical composition. Separations of ethylene-butene and ethylene-hexene copolymers were evaluated in this sorbent/solvent system by Dolle et al [68] which showed that PE with low molar mass (o20 kg/mol) is soluble in EGMBE [64] and thus may elute without retention from the column.…”
Section: Chromatographic System Based On the Precipitation-dissolutiomentioning
confidence: 99%